2017
DOI: 10.1037/men0000044
|View full text |Cite
|
Sign up to set email alerts
|

College men’s and women’s masculine gender role strain and dating violence acceptance attitudes: Testing sex as a moderator.

Abstract: The present study tested sex as a moderator of the connections between men's and women's masculine gender role strain (i.e., masculine gender role conflict and masculine gender role stress) and attitudes toward psychological, physical, and sexual male-perpetrated dating violence. Self-report measures were administered online to a large sample of male (n ϭ 398) and female (n ϭ 390) college students, and data were analyzed using structural equation modeling (SEM) procedures for testing moderation through measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 60 publications
(138 reference statements)
3
24
0
Order By: Relevance
“…Although this research does not identify specific focuses for improved intervention or prevention methods, it helps better define this societal problem by providing a more comprehensive understanding of characteristics associated with sexually aggressive beliefs and cognitions. Previous research has shown that the sexually aggressive cognitions measured in this study are correlated with sexually aggressive behaviors (Bouffard, 2010;Hill & Fischer, 2001;Humphreys, 2007;McDermott et al, 2016;Mouilso & Calhoun, 2013;Osman, 2003Osman, , 2007Truman et al, 1996;Widman & McNulty, 2010). However, as posited by feminist theories of sexual assault, societal factors related to dominance and entitlement perpetuate a culture of sexual assault.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Although this research does not identify specific focuses for improved intervention or prevention methods, it helps better define this societal problem by providing a more comprehensive understanding of characteristics associated with sexually aggressive beliefs and cognitions. Previous research has shown that the sexually aggressive cognitions measured in this study are correlated with sexually aggressive behaviors (Bouffard, 2010;Hill & Fischer, 2001;Humphreys, 2007;McDermott et al, 2016;Mouilso & Calhoun, 2013;Osman, 2003Osman, , 2007Truman et al, 1996;Widman & McNulty, 2010). However, as posited by feminist theories of sexual assault, societal factors related to dominance and entitlement perpetuate a culture of sexual assault.…”
Section: Discussionmentioning
confidence: 57%
“…Behaviors, such as sexual aggression, are the outward manifestation of underlying attitudes and personality traits (Ajzen, 2005); therefore, it is important to understand all aspects of a behavior, such as the maladaptive cognitions and personality traits associated with such behaviors and attitudes. Previous literature has attempted to understand sexual aggression from a variety of standpoints, including an evaluation of maladaptive cognitions (Bouffard, 2010; Hill & Fischer, 2001; Humphreys, 2007; Jozkowski, Peterson, et al, 2014; McDermott et al, 2016; Mouilso & Calhoun, 2013; Osman, 2003, 2007; Truman et al, 1996; Wegner et al, 2015; Widman & McNulty, 2010), specific personality disorders (e.g., psychopathy [Malamuth, 2003; Mann et al, 2010; O’Connell & Marcus, 2016; Williams et al, 2009] and narcissism [Mann et al, 2010; Mouilso & Calhoun, 2016]), environmental factors (Malamuth, 2003; Mann et al, 2010), and even broader models such as the HMC (Malamuth, 2003). However, information was lacking in some areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conforming to the previous researches, the results of a research conducted on 788 students in America show dating violence acceptance is significantly predicted by masculine gender role stress (Mcdermott et al, 2017). A meta-analysis indicates that the attitude of accepting dating violence is associated with the actual violent behavior (Vagi et al, 2013).…”
Section: Introductionmentioning
confidence: 71%
“…The failure to follow traditional gender roles resulted in feelings of distress (Mcdermott, Naylor, McKelvey, & Kantra, 2017). The presence of such distress prompts men to feel angry, anxious, increase negative affects, trigger hostility, and aggressive behavior (O'Neil & Crapser, 2011).…”
Section: Introductionmentioning
confidence: 99%